2019
DOI: 10.1152/ajplung.00110.2019
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to e-cigarettes causes inflammation and pulmonary endothelial oxidative stress in nonsmoking, healthy young subjects

Abstract: The effects of e-cigarette (e-cig) aerosol inhalation by nonsmokers have not been examined to date. The present study was designed to evaluate the acute response to aerosol inhalation of non-nicotinized e-cigarettes in terms of oxidative stress and indices of endothelial activation in human pulmonary microvascular endothelial cells (HPMVEC). Ten smoking-naïve healthy subjects (mean age ± SD = 28.7 ± 5.5 yr) were subjected to an e-cig challenge, following which their serum was monitored for markers of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 79 publications
(99 reference statements)
2
85
0
2
Order By: Relevance
“…Another study also found that parameters of lung function were impaired in e-cigarette users as compared to a control group of healthy adults [176]. Exposure to e-cigarette vapor has also been found to lead to elevated levels of oxidative stress and inflammation [177] as well as increased cardiac risk [178,179]. Thus, e-cigarette inhalation appears to have the potential to drive lung and vascular pathologies.…”
Section: In Vivo Studies On E-cigarette Liquid Exposure On Human Orgamentioning
confidence: 96%
See 1 more Smart Citation
“…Another study also found that parameters of lung function were impaired in e-cigarette users as compared to a control group of healthy adults [176]. Exposure to e-cigarette vapor has also been found to lead to elevated levels of oxidative stress and inflammation [177] as well as increased cardiac risk [178,179]. Thus, e-cigarette inhalation appears to have the potential to drive lung and vascular pathologies.…”
Section: In Vivo Studies On E-cigarette Liquid Exposure On Human Orgamentioning
confidence: 96%
“…Healthy never-smokers (before and after e-cigarette usage) Base: PG:VG (70%/30%) Nicotine: nicotine-free Flavor: flavorless Increased: oxidative stress, inflammation, circulatory burden of the serum [177] 2.…”
mentioning
confidence: 99%
“…This review included randomised controlled-trials (n=8) [31][32][33][34][35][36][37][38] ; randomised crossover studies (n=10) [39][40][41][42][43][44][45][46][47][48] ; non-randomised controlled trials (n=13) [49][50][51][52][53][54][55][56][57][58][59][60][61] and non-randomised crossover studies (n=7) [62][63][64][65][66][67][68] . These articles studied human subjects (n=24) 32,33,35,37,[39][40][41][42][43][44][45][46][47][48]56,57,[61]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only 11% of human studies investigated solely non-smoking populations. 35,41,42,61 45.8% of human studies included subjects without prior use of e-cigarettes and understanding of vaping topography (n=11), 33,35,[40][41][42]61,63,[65][66][67][68] whilst a further 33.3% of studies did not state whether subjects had previously used these devices (n=8). 37,39, [45][46][47][48]57,62 Only 45% of studies…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation